Finplan: Strategi Menuju Keluarga Sejahtera (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
The main problem for a family that is always there is usually around finances, financial management is very important in maintaining economic stability in a family, with planned financial management it will have an impact on success for the family and ease in achieving financial goals. The method of implementing the Community Service Program is by giving lectures and training in financial planning in an easy and simple way. This service activity begins with an analysis of the problem situation that occurs in partner institutions or objects of service, then it is continued with a literature review according to the problems that are given solutions through the PKM program.